Apo E gene polymorphism on development of diabetic nephropathy - Ilhan, Necip; Kahraman, Neslihan; Seckin, Dilara; Ilhan, Nevin; Colak, Ramis (Wiley, 2007)
Type 2 diabetes causes premature morbidity and mortality due to the complications of atherosclerosis and diabetic nephropathy (DN). Polymorphism of Apo E gene is known to influence lipid metabolism. Apo E is polymorphic, consisting of three common isoforms (epsilon 2, epsilon 3 and epsilon 4) encoded by three alleles (2, 3 and 4) in exon 4 on chromosome 19. The aim of this study was to investigate the effect of Apo E polymorphism as a prognostic risk factor for the development of DN. A total of 108 NIDDM patients were recruited from the Nephrology and Endocrinology Departments of our hospital. All subjects were divided into three groups: Group I: diabetes with nephropathy (n:37), group II: diabetes without nephropathy (n:71), group III: controls (n:46). Apo E genotypes were determined by real-time PCR. The epsilon 4 allele frequency was significantly higher in-group I (10.8%) than in-group III (2.2%), (p < 0.05). In diabetics without nephropathy, the total cholesterol and LDL cholesterol levels were significantly lower in subjects with epsilon 2 alleles than epsilon 3 and epsilon 4 alleles. In conclusion, the present prospective study indicates that the epsilon 4 allele of the Apo E polymorphism is one of the prognostic risk factors involved in the development of DN with type 2 diabetes mellitus. Copyright (c) 2006 John Wiley & Sons, Ltd.
Keywords: diabetic nephropathy; Apo E gene polymorphism